Pengelolaan Sarana Prasarana Pembelajaran Pendidikan Jasmani dalam Meningkatkan Hasil Belajar Peserta Didik (Studi Kasus di SMK LPS 1 Ciamis) - Abdillah, Moh Rizal; Firmansyah, Andrea Taufik; Wiguna, Candra; Herman, Maman; Suhendra, Dede Iman (Universitas Galuh, 2025)
This research was inspired by the challenges in managing physical education facilities at SMK LPS 1 Ciamis, particularly limited space and insufficient maintenance staff, which hinder the effectiveness of the learning process. The study aims to describe and analyze the planning, recording, maintenance, and supervision of sports facilities in relation to improving students’ learning outcomes. A qualitative descriptive method was employed, using observation, interviews, and documentation as data collection techniques. The informants involved were the principal, vice principals for curriculum and facilities, and the physical education teacher. The findings reveal that planning, inventory, and maintenance have been implemented according to established indicators, although weaknesses remain, such as manual administrative processes and unscheduled supervision. Overall, the management of physical education facilities has contributed positively to enhancing student achievement.This research was inspired by the challenges in managing physical education facilities at SMK LPS 1 Ciamis, particularly limited space and insufficient maintenance staff, which hinder the effectiveness of the learning process. The study aims to describe and analyze the planning, recording, maintenance, and supervision of sports facilities in relation to improving students’ learning outcomes. A qualitative descriptive method was employed, using observation, interviews, and documentation as data collection techniques. The informants involved were the principal, vice principals for curriculum and facilities, and the physical education teacher. The findings reveal that planning, inventory, and maintenance have been implemented according to established indicators, although weaknesses remain, such as manual administrative processes and unscheduled supervision. Overall, the management of physical education facilities has contributed positively to enhancing student achievement.This research was inspired by the challenges in managing physical education facilities at SMK LPS 1 Ciamis, particularly limited space and insufficient maintenance staff, which hinder the effectiveness of the learning process. The study aims to describe and analyze the planning, recording, maintenance, and supervision of sports facilities in relation to improving students’ learning outcomes. A qualitative descriptive method was employed, using observation, interviews, and documentation as data collection techniques. The informants involved were the principal, vice principals for curriculum and facilities, and the physical education teacher. The findings reveal that planning, inventory, and maintenance have been implemented according to established indicators, although weaknesses remain, such as manual administrative processes and unscheduled supervision. Overall, the management of physical education facilities has contributed positively to enhancing student achievement.